2018
DOI: 10.1038/s41586-018-0465-8
|View full text |Cite
|
Sign up to set email alerts
|

Widespread intronic polyadenylation inactivates tumour suppressor genes in leukaemia

Abstract: DNA mutations are known cancer drivers. Here we investigated whether mRNA events that are upregulated in cancer can functionally mimic the outcome of genetic alterations. RNA sequencing or 3'-end sequencing techniques were applied to normal and malignant B cells from 59 patients with chronic lymphocytic leukaemia (CLL). We discovered widespread upregulation of truncated mRNAs and proteins in primary CLL cells that were not generated by genetic alterations but instead occurred by intronic polyadenylation. Trunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
203
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(209 citation statements)
references
References 47 publications
5
203
0
1
Order By: Relevance
“…These results mirror the effects seen in zebrafish mutants carrying a heterozygous foxn3 loss-of-function allele where a 50% reduction in foxn3 transcript was accompanied by a twofold increase in mycb transcript (Karanth et al, 2018). These effects are also similar to that observed when immortalized human cells are transduced with a dominant-negative FOXN3 cDNA that occurs in leukemia as a consequence of pathological intron polyadenylation (Lee et al, 2018). Knock-down of Foxn3 in mouse livers decreased fasting blood glucose (Fig.…”
Section: Resultssupporting
confidence: 76%
“…These results mirror the effects seen in zebrafish mutants carrying a heterozygous foxn3 loss-of-function allele where a 50% reduction in foxn3 transcript was accompanied by a twofold increase in mycb transcript (Karanth et al, 2018). These effects are also similar to that observed when immortalized human cells are transduced with a dominant-negative FOXN3 cDNA that occurs in leukemia as a consequence of pathological intron polyadenylation (Lee et al, 2018). Knock-down of Foxn3 in mouse livers decreased fasting blood glucose (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Many previous reports have shown that introns influence human diseases. These diseases fall into two broad classes: heritable diseases (RILEY AND KRIEGER 2005;SWARBRICK et al 2011;VAZ-DRAGO et al 2017) and cancers (HSU et al 2015;JUNG et al 2015;WIESNER et al 2015;NERI et al 2017;LEE et al 2018). The intron-dependent processes that are affected often unknown, poorly understood, or if understood, lack experimental means to determine how to suppress the intron-related pathology.…”
Section: Understanding the Role Of Introns In Human Diseasementioning
confidence: 99%
“…At the same time, a large proportion of data mapped to non-coding region was noticed, including both intronic and intergenic regions. These reads suggest that there may be complex post-transcriptional regulation mechanisms occurring in the cells that has been previously underappreciated, but which EASY RNAseq may be able to successfully detect (11)(12)(13)(14).…”
Section: Easy Rnaseq Is Highly Reproducible At Low Sample Input Levelsmentioning
confidence: 89%